(untitled) (Journal of Human Sciences, 2022)
The lack of cash flow constitutes a phenomenon of concern and concern ,due to several reasons whether at the political, security or economic Levels , but its negative effects were severe and dangerous ,threatening the social , economic and political stability in Libyan society. The severity of the damage caused by the lack of cash has increased many satisfactory social deviation ,as it represents a deep social problem that deserves greater attention by sociology and sheds light on its various aspects , especially in light of the low standard of living from which most families in Libyan society , which led to the emergence of disadvantaged groups in difficult conditions , as poverty plays a role in difficult conditions , as poverty plays a role in deviation tion , but it can help to create a set of social and psychological conditions that may lead to the weakening of the moral lead to the weakening of the moral sense, which represents a bulwark against deviation . The family has an important role in settling the event or its deviation ,and it seems difficult to play its role as it should in instilling social values in the hearts of its chidren that work on building their par sonelity, in light of the material difficulties that stand in the way of improving their conditions and work to create the appropriate atmosphere for deriation. This , was the reason for choosing the topic of cash shortage because it is closer to reality and closer to understanding , as well as revealing the role of cash shortage within the family . The aim of the research is to highlight the research is to highlight the relationship between cash shortage and social deviation , the research relied on the descriptive analytical approach because it suits the nature of the study and suits the social reality . From the heads of families , the new locality in the city of Sabah was taken as a spatial field for the study ,while the human field was represented in a random sample consisting of (140) individual heads of individual heads of families who were chosen at random . The most important search results : • There are statistically significant differences in the role of lack of cash flow on the spread of social due to the gender variable , these differences are statistically significant in the first axis ] family problems [ ,and the difference are in favor of females, as well as statistically significant in the total axes ]social deviation [ , in favor of females as well. • There are differences in the respondents ,attitudes about the role of cash shortage in the spread of social deviation due to the monthly income variable ,the first axis was not statistically significant, and the second axis ] security problems [ was statistically significant , while the total axes were also not significant .